EXCLUSION OF ILLEGALITY IN THE CRIME OF UNAUTHORIZED WIRETAPPING AND RECORDING - Radmanović, Jelena S (Glasnik Advokatske komore Vojvodine, 2025)
The criminal act of unauthorized wiretapping and recording has long been an integral part of the corpus of criminal acts incriminated in domestic criminal legislation. Until now, due to its peculiarities, specifically the fact that for the basic forms of this crime proscribed under Article 143, paragraphs 1 and 2, prosecution is undertaken through private lawsuit, it has not occurred particularly often in practice. However, with the development of technology, the possibilities for the execution of this criminal offense increase significantly, since today every average citizen has the means, that is, the devices suitable for the execution of this criminal offense. For the stated reason, it is necessary to analyze in detail the individual elements of this criminal act, in order to avoid uneven interpretation and application in practice. In addition, it is necessary to set the limits of the criminal law with regard to this act, since the values that are protected by it in certain situations are not more important than the values that can be protected by violating them. For the stated reason, it is necessary to prescribe special conditions for the exclusion of illegality, the content of which the paper will try to propose.